Material needs insecurity and dietary salt - Role in uncontrolled hypertension: A case-Control study - Alfia Rachel Kaki; Jayaprakash Muliyil; Arun Jose Nellickal; Visakakshi Jeyaseelan; Vijay Prakash Turaka; Anand Zachariah; Samuel George Hansdak; Manjeera Jagannati; Thambu David Sudarsanam (Wolters Kluwer Medknow Publications, 2021)
We performed a case control study of 108 patients for the risk of uncontrolled hypertension Housing insecurity, a part of material needs insecurity is an independent predictor of uncontrolled hypertension (adjusted odds ratio 29.9, 1.2-734). Food insecurity, cost related medication underuse and housing instability were seen in 32.4%, 33.3%.and 39.8% of our study subjects respectively. On average patients had 6 stressful life events, which was not different among those with different levels of blood pressure control. We did not find correlation with 24-urine sodium excretion, a reflection of salt intake and hypertension control. The average hypertensive subject was taking more than 10 grams of sodium per day, far higher than recommended.